PENINGKATAN KETERAMPILAN MENULIS TEKS DESKRIPSI MENGGUNAKAN MEDIA GAMBAR PADA KELAS VIIB SMPN 4 SUNGAI RAYA - Khairullah, Khairullah; Sabila, Lisa (Universitas Tanjungpura, 2025)
Writing is one of the language skills that is still less favored among students. One effort to improve students' writing skills is by using interesting learning media, one of which is visual media. This research aims to describe the use of visual media in teaching descriptive text writing. The research method used is descriptive qualitative with data collection techniques in the form of test, interviews, observation, and documentation. The sample in this study consisted of 30 students from class VII B at SMP Negeri 4 Sungai Raya. The results of the research show an improvement in students' writing skills after using visual media in teaching descriptive text. This improvement is evidenced by the data obtained, starting from the pre-cycle, where 5 students (16.7%) complete and 25 students (83.3%) did not complete, in Cycle I, 22 students (73.3%) complete and 8 students (26.7%) did not complete, and in Cycle II, there were 29 students (96.6%) who complete and 1 student (3.4%) who did not complete. The conclusion drawn is that the use of visual media, whether in the form of photos or using an LCD projector screen, can improve the writing skills of descriptive text for students in class VII B at SMP Negeri 4 Sungai Raya.